A contribution to the tick (Acari: Ixodidae) fauna of Turkey: The first record of Ixodes inopinatus Estrada-Peña, Nava & Petney - (:unkn) unknown (My University, 2020)
Ticks are blood-sucking ectoparasites of terrestrial vertebrates. The genus Ixodes Latreille is the largest among hard ticks, and the members of the genus are spread around the world. In the present study, we reported presence of Ixodes inopinatus Estrada-Peña, Nava & Petney, 2014 in Turkey for the first time. The specimens of I. inopinatus (1 male, 6 females) were collected from cattle in Ordu province, Turkey.